Borrelia burgdorferi serine protease HtrA is a pleiotropic regulator of stress response, motility, flagellar hemostasis, and infectivity - Kai Zhang; Ching Wooen Sze; Hang Zhao; Jun Liu; Chunhao Li (Communications Biology)
Abstract High-temperature requirement protease A (HtrA) is a family of serine proteases that regulate bacterial stress response through controlling protein quality. This report shows that the Lyme disease bacterium Borrelia burgdorferi HtrA has a pleiotropic role in regulation of bacterial stress response, motility, flagellar hemostasis, and infectivity. Loss-of-function study first shows that a deletion mutant of htrA (∆htrA) fails to establish an infection in a murine model of Lyme disease. Interestingly, this defect can be restored only with its endogenous promoter. Follow up mechanistic study reveals that the expression of htrA varies under different growth conditions and is finely regulated and that deletion of htrA leads to dysregulation of several key virulence determinants of B. burgdorferi. We also find that deletion of htrA abrogates the ability of B. burgdorferi to survive at high temperatures and that the ∆htrA mutant has defects in locomotion as the expression of several key chemotaxis proteins are significantly downregulated. Cryo-electron tomography analysis further reveals that deletion of htrA disrupts flagellar homeostasis, e.g., the mutant has short and misplaced flagella that fail to form a ribbon-like structure to propel bacterial locomotion. This report provides new insights into understanding the role of HtrA in spirochetes.